DEVELOPMENT AND CHARACTERIZATION OF NANOPARTICLE-BASED DRUG DELIVERY SYSTEMS - Mungle, Archana N.; Daf, Abhijit N.; Parate, Vaishali Tilakchand; Kapse, Akash S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the application of nanoparticles, drug delivery has enhanced so much, as the problems of conventional medicines are resolved. Problems of the normal drug formulations such as poor solubility, low absorption, rapid degradation and undesired side effects are usual. Due to their extreme smallness (1-100 nm) and high surface area nanoparticles make possible targeted and restricted release of drugs. This research synthesized nanoparticles using polymer carriers that were biodegradable, containing model drug and analyzed the size, shape, surface charge, drug loading, and release patterns of these particles. Characterization was done using tests such as DLS, SEM and zeta potential. The outcome revealed the homogenous particle size, excellent drug loading, and a low drug release over 24 hours. Nanoparticles in general enhanced drug stability and decreased side effects as well as offering targeting capabilities that were not as successful through conventional methods. In the future, a study of the animal models, long-term stability and surface modifications should be done to achieve better results.